Efectividad agronómica y económica de la nutrición foliar en maíz amarillo duro de secano - Vera Meza, Jonathan Gabriel (2022)
The aim of the research was to evaluate the agronomic and economic effectiveness of complementary foliar fertilization in dry hard yellow corn. The work was carried out during the rainy season of 2021, at the Figueroa site, Manabí, Ecuador. The treatments evaluated were: Edaphic nitrogen, phosphorus and potassium (NPK) fertilization complemented with foliar application of mineral nutrients and biostimulants (T1), NPK soil fertilization (T2) and a control treatment with nitrogen omission (T3). A randomized complete block design with seven replicates and 21 experimental units of 24 m2 was used. Data were analyzed through ANOVA and separation of means with Tukey's test α = 0.05. Grain yield (GY), agronomic efficiency of N (AEN) and the net economic benefit of fertilization (NEB) were recorded. The complementary foliar fertilization increased the GY by 16.45 and 56.93%, with respect to the NPK and control edaphic fertilization treatments. In the same way, the foliar application increased the AEN by 28.89%, in relation to the NPK soil fertilization. Finally, the complementary foliar fertilization produced the highest NEB, with an increase of 376 USD ha-1, in relation to the NPK edaphic fertilization treatment. Complementary foliar fertilization enhanced the effect of NPK edaphic fertilization and increased yield, profitability and EAN in rainfed maize.